2019
DOI: 10.4103/jmau.jmau_64_18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes toward the use of anabolic-androgenic steroids among the population of Jeddah, Saudi Arabia

Abstract: Purpose: The aim of this study was to investigate the correlation between the use of anabolic-androgenic steroids (AASs) among the population of Jeddah, Saudi Arabia, and their knowledge and attitudes. Methods: This was a community-based, cross-sectional observational study. This study was conducted using a questionnaire that was distributed among the population during the period from February 3, 2018, to February 25, 2018. This questionnaire comprised 31 questions, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Our study confirmed the increasing global trend of AAS abuse in the young population; the largest user population in our study was 20–40 years old, consistent with results from other global and regional studies, such as those conducted in Saudi Arabia (Maha et al, 2019 ). Surprisingly, despite cultural differences worldwide, the aims of AAS users are almost identical.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirmed the increasing global trend of AAS abuse in the young population; the largest user population in our study was 20–40 years old, consistent with results from other global and regional studies, such as those conducted in Saudi Arabia (Maha et al, 2019 ). Surprisingly, despite cultural differences worldwide, the aims of AAS users are almost identical.…”
Section: Discussionsupporting
confidence: 92%
“…Even though the AAS abuse is underreported in many communities, and up to 50% of AAS users do not disclose their use to their physician, it is becoming an alarming global phenomenon and well noticed in many regional and global communities (Cohen et al, 2007 ; Graham et al, 2008 ; Maha et al, 2019 ; Pany & Panigraphy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…AAS abusers' attitudes were explored in our study, including their knowledge about the adverse effects of AAS abuse on sexual and fertility health as most of respondents believed their patients are less knowledgeable or had misconceptions about the AAS adverse effects. This finding also was acknowledged by Ahmed et al study 20 in Jeddah/Saudi Arabia Kingdom who concluded that half of included patients exhibited poor knowledge regarding the side effects of AASs. These are alarming factors, proving the underestimation of AAS adverse effects, thereby raising the urgent need of national awareness programs to provide the knowledge and explanation of adverse effects of AAS abuse and to have better‐governed control over dispensing these medications.…”
Section: Discussionsupporting
confidence: 52%
“…knowledgeable or had misconceptions about the AAS adverse effects. This finding also was acknowledged by Ahmed et al study20 in Jeddah/Saudi Arabia Kingdom who concluded that half of included patients exhibited poor knowledge regarding the side effects of AASs. These are alarming factors, proving the underestimation of AAS adverse effects, thereby raising the urgent need of nationalT A B L E 2…”
supporting
confidence: 52%
“…AASs were made for the sole purpose of treating medical conditions like steroid hormone deficiency, such as delayed puberty, in addition to diseases that cause significant loss of lean muscle mass, like cancer and AIDS patients [ 3 ]. They have also been prescribed to treat hereditary angioedema, which causes swelling of the face, arm, leg, throat, windpipe, intestines, and/or sexual organs, as well as to assist in the treatment of some types of anemia and certain types of breast cancer in some women [ 6 , 7 ]. Bodybuilders and athletes, both recreational and professional, have abused AASs to improve their performance, strength, and endurance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%